PENGARUH BUDAYA PERUSAHAAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DANA PENSIUN PERTAMINA DI JAKARTA - Sumarsid Sumarsid (CKI ON SPOT, 2017)
In  this  study  the  authors  analyzed  to  determine  the  effect  of  corporate  culture  and  motivation  on employee  performance  improvement  Pension  Fund.  From  the  analysis  of  multiple  correlation  coefficients obtained a correlation coefficient Culture Company X1 and X2 correlation coefficient Motivation to employee performance is 0950, thus the corporate culture and motivation strong and significant influence 0,000 <0.05 on the performance of the employee pension fund of Pertamina in Jakarta. Results of analysis of the coefficient of determination (R2) = 0.903 thus the corporate culture and motivation have contributed 90.3% to the Pension Fund employee performance in Jakarta, and the remaining 9.7% are influenced by other factors were not the authors  carefully,  including  discipline  ,  leadership,  and  quality  of  human  resources.  Based  on  the  results  of research by F test showed that the corporate culture and motivation simultaneously significant effect on employee performance improvement DPP (Pension Fund) in Jakarta, because sig. F count is 0000, meaning <5% (0.000 <0.005). Thus Ho rejected and Ha accepted. Based on testing with the t variable X1 is the corporate culture of - 0.222 with t table is 1,701 and the value of the variable significant corporate culture X1 0.826> 5%, thereby to> tα then Ha (alternative hypothesis) refused and Ho (null hypothesis) is accepted , This means that the corporate culture  is  partially  no  significant  effect  on  employee  performance  DPP  (Pension  Fund)  in  Jakarta.  While  the value of t count X2 motivation of 11 494 with the value t table is 1,701 and significant value for the variable X2 motivation 0000> 5%, thereby to <tα, That X2 motivation partially significant effect on employee performance Pension Fund in Jakarta.